Dukungan teman sebaya dengan harga diri pada remaja - Ayuni Wulandari; Fiki Wijayanti (Health Sciences and Pharmacy Journal, 2023)
Self-esteem is an individual's assessment of oneself either positively or negatively which can be influenced by interactions with people, namely attitudes, self-esteem, self-acceptance, and the treatment of others. Peer support can affect self-esteem in adolescents. Peer support can be obtained from social support which can increase self-esteem in adolescents. The research objective is to determine the relationship between peer support and self-esteem in adolescents at SMA N 1 Bergas. This study used a descriptive correlation with a cross-sectional approach. The population in this study was 1,210 students. The technique for collecting data was quota sampling and the research sample was 292 students at SMA N 1 Bergas. The research instrument used the RSE questionnaire. The analysis used the Kendall Tau test. The results showed that 198 students had high peer support, 181 students had high self-esteem, and there was a significant relationship between peer support and selfesteem in adolescents at SMA N 1 Bergas (p-value = 0.033) (0) .05), and τ = +0.124. The higher peer support is given, the higher self-esteem existed in adolescents. There is a relationship between peer support and self-esteem in adolescents at SMA N 1 Bergas. Suggestions for adolescents are to increase peer support so that adolescents are more confident.